THE DISTANT CREATIVE EXAMINATION FOR UNIVERSITY ENTRANTS - Anton V. Dozhdikov (Высшее образование в России)
The paper focuses on mechanism improving the effectiveness of entrance competitive examination to select students for University admission. The author dwells on such form of entrance competitions as a distant creative examination. Distant creative examination for entrants is the basic element of a «society of equal starting opportunities» leveling geographical, territorial, socio-economic, corruption, psychological, and other objective and subjective barriers for young people on admission to the organization of higher education. The paper discusses the main idea of distant creative examination, its purposes and the mechanism of implementation. Special attention is paid to the problem of the objective assessment, the necessary conditions and requirements.